(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This article discusses the changes in the social basis of society in the current conditions of strengthening market relations, the moral and aesthetic culture of management in society, the factors of its formation, the contradictions in the process of moral and aesthetic culture.